An organic solar cell and a preparation method and application thereof

CN115915783BActive Publication Date: 2026-10-16BEIHANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211449653.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-18
Publication Date
2026-10-16
Estimated Expiration
2042-11-18

AI Technical Summary

Technical Problem

然而,目前的有机太阳能电池在综合性能方面仍存在明显的不足之处,转化效率偏低,阻碍了OPV器件的进一步发展

Benefits of technology

[0054] In the organic solar cell provided by this invention, the incorporation of di(pentafluorophenyl)zinc, a Lewis acid small molecule material, into the photoactive layer improves the morphology of the photoactive layer, reduces its surface roughness, optimizes the contact between the photoactive layer and the first and second buffer layers, and effectively adjusts the microscopic donor-acceptor phase separation. This enhances the carrier mobility of the photoactive layer, promotes charge transport, significantly improves the transport efficiency of photogenerated carriers, strengthens the dissociation and transport capabilities of photogenerated excitons, and suppresses carrier recombination. Consequently, the short-circuit current and photoelectric conversion efficiency of the organic solar cell are significantly improved, with a short-circuit current of 25.68-27.21 mA/cm² under standard test conditions. 2 The photoelectric conversion efficiency (PCE) is ≥16.23%, reaching 16.97%, demonstrating superior overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115915783B_ABST
    Figure CN115915783B_ABST
Patent Text Reader

Abstract

The application provides an organic solar cell, a preparation method and application thereof. The organic solar cell comprises a conductive substrate, a first buffer layer, a photoactive layer, a second buffer layer and a metal electrode which are sequentially arranged. The material of the photoactive layer comprises a combination of an electron donor material, an electron acceptor material and bis(pentafluorophenyl)zinc. The application incorporates bis(pentafluorophenyl)zinc into the photoactive layer, improves the morphology of the photoactive layer, reduces the surface roughness, optimizes the contact between the photoactive layer and the first buffer layer and the second buffer layer, effectively adjusts the micro donor-acceptor phase separation, improves the carrier mobility of the photoactive layer, promotes the charge transport, improves the transport efficiency of the photo-generated carriers, enhances the ability of photo-generated exciton dissociation and transport, and inhibits the carrier recombination, so that the short-circuit current and the photoelectric conversion efficiency of the organic solar cell are significantly improved, and the comprehensive performance is more excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solar cell technology, specifically relating to an organic solar cell, its preparation method, and its application. Background Technology

[0002] Fossil fuels such as oil, coal, and natural gas have been the primary energy sources for centuries. However, fossil fuels are finite, and their combustion produces carbon dioxide and other pollutants. Therefore, developing clean, green, and renewable energy sources is one of the most important research topics of the 21st century. Biomass energy, wind energy, fuel cells, and solar energy are currently the most promising technologies for producing renewable energy, and converting solar energy into electricity is one of the most interesting areas of research in this field. Organic solar cells (OSCs) have attracted widespread attention in the industry due to their potential advantages, including light weight, low production cost, ease of processing, flexibility, and higher molecular absorption coefficient.

[0003] Over the past few decades, bulk heterojunction solar cells based on polymer donors and fullerene derivative acceptors have dominated the field of organic photovoltaic (OPV) research. For example, CN112259687A discloses a ternary fullerene organic solar cell. In the active layer of a binary fullerene bulk heterojunction organic solar cell composed of polymer donor material PTB7-Th and fullerene acceptor material PC71BM, a (A'-D)2A type small molecule donor material TiC8 based on asymmetric thiopheneisobenzopyran is added, constructing a type of ternary fullerene organic solar cell with a PTB7-Th:TiC8:PC71BM active layer. Compared with binary fullerene organic solar cells, this organic solar cell has improved energy conversion efficiency and stability. CN109449297A discloses an organic solar cell structure based on polypropylene as the ternary element. The ternary organic active layer comprises a polymer, a fullerene derivative, and polypropylene. The use of polypropylene enables good efficiency even with a relatively thick active layer and reduces the size of PC71BM aggregates in the ternary active layer, thus improving the active layer morphology. However, with the development of OPV technology, until a few years ago, the inherent drawbacks of fullerene derivatives, such as high production cost, narrow absorption range, low light absorption coefficient, difficult purification, and poor bandgap tunability, limited further improvements in conversion efficiency.

[0004] In recent years, organic solar cells using non-fullerene small molecule materials as acceptors have developed rapidly. The use of star molecules such as Y6 and N3 non-fullerene acceptors has led to breakthroughs in the performance of organic photovoltaic devices. For example, CN114256421A discloses a flexible organic solar cell comprising a flexible transparent electrode, an electron transport layer, an active layer, a hole transport layer, and an anode layer. The active layer comprises a mixture of PM6 and the non-fullerene acceptor Y6 or its derivatives, or a mixture of PM6 and PC61BM with Y6, giving the flexible organic solar cell good stability and efficiency. However, current organic solar cells still have significant shortcomings in overall performance, with low conversion efficiency, hindering the further development of OPV devices. Therefore, improving the performance of organic solar cells and promoting higher conversion efficiency is a key research focus in this field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide an organic solar cell, its preparation method, and its application. By doping with di(pentafluorophenyl)zinc, the morphology and performance of the photoactive layer are significantly optimized, enhancing the charge migration and transport capabilities of the organic solar cell, effectively improving its short-circuit current and photoelectric conversion efficiency, and giving it better overall performance.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides an organic solar cell, the organic solar cell comprising a conductive substrate, a first buffer layer, a photoactive layer, a second buffer layer and a metal electrode arranged sequentially; the photoactive layer is made of a combination of an electron donor material, an electron acceptor material and di(pentafluorophenyl)zinc.

[0008] This invention employs molecular doping to improve carrier transport and interface properties. The increased background carrier concentration caused by doping may increase the recombination rate of bimolecular charges, and the improved charge injection can reduce the device's rectification properties. In the organic solar cell provided by this invention, the Lewis acid small molecule material di(pentafluorophenyl)zinc is incorporated into the photoactive layer. This optimizes the morphology of the photoactive layer, reduces its surface roughness, and improves the contact between the photoactive layer and the first and second buffer layers. Furthermore, the doping of di(pentafluorophenyl)zinc effectively adjusts the microscopic donor-acceptor phase separation, enhancing the carrier mobility of the photoactive layer, promoting charge transport in the organic solar cell, significantly improving the transport efficiency of photogenerated carriers, enhancing the dissociation and transport capabilities of photogenerated excitons, and suppressing carrier recombination. Consequently, the short-circuit current and photoelectric conversion efficiency of the organic solar cell are significantly improved, resulting in superior overall performance. Moreover, the preparation of di(pentafluorophenyl)zinc is simple, inexpensive, and essentially non-toxic and pollution-free, which is beneficial for the large-scale fabrication of high-performance, low-cost organic solar cells.

[0009] In this invention, the structure of the di(pentafluorophenyl)zinc is as follows: It is denoted as ZnCF.

[0010] Preferably, based on the total mass of the electron donor material and the electron acceptor material as 100%, the mass of the bis(pentafluorophenyl)zinc is 0.0005-0.01%, for example, it can be 0.0006%, 0.0008%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, or 0.009%, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0011] As a preferred technical solution of the present invention, by controlling the doping ratio of the di(pentafluorophenyl)zinc in the photoactive layer, the phase separation of the donor and acceptor in the photoactive layer can be effectively adjusted, the morphology of the photoactive layer can be optimized, the carrier mobility can be improved, thereby enhancing the ability of photogenerated excitons to dissociate and transport, suppressing the carrier recombination ability, and greatly improving the performance of the organic solar cell.

[0012] Preferably, the electron donor material includes polymeric electron donor materials, including but not limited to: any one or a combination of at least two of the following: poly(p-phenyleneethylene), poly(p-phenylene), polythiophene, polyquinoline, porphyrin, phthalocyanine, and polymers containing electron-withdrawing conjugated units and electron-donating conjugated units.

[0013] Preferably, the electron donor material comprises a polymer containing electron-withdrawing conjugated units and electron-donating conjugated units.

[0014] For example, the electron-withdrawing conjugating unit includes any one or a combination of at least two of pyrrolopyrroledione (DPP), benzothiadiazole (BT), thienopyrroledione (TPD), and thienothiophene (TT); the electron-donating conjugating unit includes any one or a combination of at least two of dithienobenzene, carbazole, fluorene, dibenzothiophene, and dibenzofuran.

[0015] Preferably, the electron donor material comprises PM6, with the following structure: Wherein, R is 2-ethylhexyl.

[0016] Preferably, the electron acceptor material comprises a small molecule electron acceptor material.

[0017] Preferably, the electron acceptor material comprises N3, and its structure is as follows:

[0018] Preferably, the mass ratio of the electron donor material to the electron acceptor material is 1:(0.2-5), for example, it can be 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.5, 1:3, 1:3.5, 1:4 or 1:4.5, etc., more preferably 1:(1-1.5), and even more preferably 1:1.2.

[0019] Preferably, the photoactive layer is a bis(pentafluorophenyl)zinc doped PM6:N3 active layer.

[0020] Preferably, the thickness of the photoactive layer is 50-250nm, for example, it can be 60nm, 80nm, 100nm, 110nm, 130nm, 150nm, 170nm, 190nm, 200nm, 220nm or 240nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0021] Preferably, the conductive substrate is an ITO (indium tin oxide) conductive substrate.

[0022] Preferably, the conductive substrate includes a conductive layer (as an electrode) and a substrate, wherein the conductive layer is an ITO layer.

[0023] Preferably, the material of the first buffer layer is a hole transport material.

[0024] Preferably, the hole transport material comprises any one or a combination of at least two of the following: polyphenylene oxide, polyaniline (Pani), poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS), or aromatic amine compounds.

[0025] Preferably, the material of the first buffer layer includes PEDOT:PSS.

[0026] Preferably, the thickness of the first buffer layer is 20-40nm, for example, it can be 21nm, 23nm, 25nm, 27nm, 29nm, 30nm, 31nm, 33nm, 35nm, 37nm or 39nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, but 20-30nm is further preferred.

[0027] Preferably, the material of the second buffer layer is an electron transport material.

[0028] Preferably, the material of the second buffer layer includes PFN-Br and / or PNDIT-F3N, and more preferably PNDIT-F3N.

[0029] Preferably, the thickness of the second buffer layer is 10-20nm, for example, it can be 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm or 19nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0030] Preferably, the material of the metal electrode includes any one or a combination of at least two of calcium, magnesium, barium, aluminum, silver, gold, copper, nickel, zinc, titanium, manganese, iron, platinum or molybdenum, and more preferably includes any one or a combination of at least two of silver, gold and copper.

[0031] Preferably, the thickness of the metal electrode is 70-120nm, for example, it can be 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm or 115nm, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0032] In a second aspect, the present invention provides a method for preparing an organic solar cell as described in the first aspect, the method comprising: sequentially coating a first buffer layer material on a conductive layer of a conductive substrate, performing a first annealing treatment, coating a photoactive layer material, performing a second annealing treatment, coating a second buffer layer material, and setting a metal electrode to obtain the organic solar cell.

[0033] Preferably, the method of coating the first buffer layer material includes spin coating.

[0034] Preferably, the temperature of the first annealing treatment is 150-180℃, for example, it can be 152℃, 155℃, 158℃, 160℃, 162℃, 165℃, 168℃, 170℃, 172℃, 175℃ or 178℃, and specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, and 160-170℃ is further preferred.

[0035] Preferably, the first annealing treatment time is 5-30 min, for example, it can be 6 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min or 28 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific point values ​​included in the range, and 10-20 min is further preferred.

[0036] Preferably, the method for coating the photoactive layer material includes: drop-coating or spin-coating a solution of the photoactive layer material.

[0037] Preferably, the sum of the concentrations of the electron donor material and the electron acceptor material in the solution is 10-30 mg / mL, for example, it can be 11 mg / mL, 13 mg / mL, 15 mg / mL, 17 mg / mL, 19 mg / mL, 20 mg / mL, 21 mg / mL, 23 mg / mL, 25 mg / mL, 27 mg / mL or 29 mg / mL, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0038] Preferably, the solvent of the solution includes any one or a combination of at least two of chloroform, chlorobenzene, o-dichlorobenzene or o-xylene, with chloroform being more preferred.

[0039] Preferably, the solution further includes an additive, which includes any one or a combination of at least two of chloronaphthalene, diiodooctane or diphenyl ether, with chloronaphthalene being more preferred.

[0040] Preferably, the volume percentage of the additive in the solution is 0.1-1%, for example, it can be 0.2%, 0.3%, 0.4%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, or 0.95%, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, but it is more preferably 0.5-1%.

[0041] Preferably, the temperature of the second annealing treatment is 80-100℃, for example, it can be 81℃, 83℃, 85℃, 87℃, 89℃, 90℃, 91℃, 93℃, 95℃, 97℃ or 99℃, and specific values ​​between the above points. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, and 85-95℃ is further preferred.

[0042] Preferably, the second annealing time is 5-20 min, for example, it can be 6 min, 8 min, 10 min, 11 min, 13 min, 15 min, 17 min or 19 min, as well as specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range.

[0043] Preferably, the method of coating the second buffer layer material includes spin coating.

[0044] Preferably, the solution of the second buffer material is coated onto the photoactive layer using a spin-coating method.

[0045] Preferably, the solvent of the solution includes methanol.

[0046] Preferably, the method for setting the metal electrode includes vapor deposition.

[0047] Preferably, the preparation method specifically includes the following steps:

[0048] (1) Spin-coat the first buffer layer material onto the conductive layer of the conductive substrate, and anneal at 150-180℃ for 5-30 minutes to obtain the first buffer layer;

[0049] (2) A solution of photoactive layer material is drop-coated or spin-coated onto the first buffer layer obtained in step (1), and annealed at 80-100℃ for 5-20 min to obtain a photoactive layer; the sum of the concentrations of electron donor material and electron acceptor material in the solution is 10-30 mg / mL;

[0050] (3) Spin-coat the second buffer layer material onto the photoactive layer obtained in step (2), and dry it to obtain the second buffer layer;

[0051] (4) Deposit metal onto the second buffer layer obtained in step (3) to obtain a metal electrode and obtain the organic solar cell.

[0052] Thirdly, the present invention provides a photovoltaic module, the photovoltaic module comprising the organic solar cell as described in the first aspect.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] In the organic solar cell provided by this invention, the incorporation of di(pentafluorophenyl)zinc, a Lewis acid small molecule material, into the photoactive layer improves the morphology of the photoactive layer, reduces its surface roughness, optimizes the contact between the photoactive layer and the first and second buffer layers, and effectively adjusts the microscopic donor-acceptor phase separation. This enhances the carrier mobility of the photoactive layer, promotes charge transport, significantly improves the transport efficiency of photogenerated carriers, strengthens the dissociation and transport capabilities of photogenerated excitons, and suppresses carrier recombination. Consequently, the short-circuit current and photoelectric conversion efficiency of the organic solar cell are significantly improved, with a short-circuit current of 25.68-27.21 mA / cm² under standard test conditions. 2 The photoelectric conversion efficiency (PCE) is ≥16.23%, reaching 16.97%, demonstrating superior overall performance. Attached Figure Description

[0055] Figure 1 This is a schematic diagram of the structure of the organic solar cell provided in Example 1;

[0056] Wherein, 10-conductive substrate, 11-conductive layer, 12-substrate, 20-first buffer layer, 30-photoactive layer, 40-second buffer layer, 50-metal electrode;

[0057] Figure 2 The above is a comparison chart of the IV test curves of the organic solar cells provided in Examples 1-3 and Comparative Example 1. Detailed Implementation

[0058] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0059] In the following specific embodiments of the present invention, the raw materials and reagents involved are all commercially available products, or can be prepared by methods known in the prior art.

[0060] Example 1

[0061] An organic solar cell and its fabrication method are disclosed. A schematic diagram of the structure of the organic solar cell is shown below. Figure 1As shown, the structure includes a conductive substrate 10, a first buffer layer 20, a photoactive layer 30, a second buffer layer 40, and a metal electrode 50, arranged sequentially. The conductive substrate 10 includes a conductive layer 11 and a substrate 12, with the conductive layer 11 in contact with the first buffer layer 20. The conductive substrate 10 is an ITO transparent conductive substrate. The first buffer layer 20 is made of PEDOT:PSS and has a thickness of 25 nm. The photoactive layer 30 is made of PM6, N3, and zinc di(pentafluorophenyl)zinc (ZnCF), with a PM6 to N3 mass ratio of 1:1.2 and a ZnCF doping mass of 0.01% (based on a 100% mass ratio of PM6 and N3), and a thickness of 100 nm. The second buffer layer 40 is made of PNDIT-F3N and has a thickness of 15 nm. The metal electrode 50 is made of silver and has a thickness of 80 nm.

[0062] The method for preparing the organic solar cell includes the following steps:

[0063] (1) The ITO transparent conductive substrate was ultrasonically cleaned for 15 min with ultrapure water, acetone and isopropanol respectively. After cleaning, it was dried with high-purity nitrogen and then treated in a UV ozone cleaner for 15 min. The PEDOT:PSS solution was filtered with a water filter and spin-coated onto the ITO conductive layer of the ITO transparent conductive substrate. The spin-coating speed was 4000 rpm and the spin-coating time was 30 s. Then it was annealed at 150℃ for 15 min to obtain a first buffer layer with a thickness of 25 nm.

[0064] (2) Electron donor material PM6 and electron acceptor material N3 are mixed at a mass ratio of 1:1.2 and dissolved in chloroform to make the sum of the concentrations of PM6 and N3 in the solution 16 mg / mL. Chloronaphthalene with a volume percentage of 0.5% is added to the solution and stirred evenly. Zinc di(pentafluorophenyl) is added with a mass of 0.01% based on the sum of the mass of PM6 and N3 as 100% to prepare a solution of photoactive layer material with a doping concentration of 0.01%. The solution of photoactive layer material is coated onto the surface of the first buffer layer by spin coating at a spin coating speed of 3200 rpm and a spin coating time of 40 s. Afterward, it is annealed at 90°C for 10 min to obtain a photoactive layer with a thickness of 100 nm.

[0065] (3) Spin-coating the PNDIT-F3N solution onto the photoactive layer and drying it to obtain a second buffer layer with a thickness of 15 nm.

[0066] (4) 80 nm of metallic silver is deposited on the surface of the second buffer layer as a metal electrode to obtain the organic solar cell.

[0067] Example 2

[0068] An organic solar cell and its preparation method are disclosed, which differ from Example 1 only in that the doping mass of ZnCF is 0.001% (based on the mass sum of PM6 and N3 being 100%); the types of other materials, device structure and thickness, and preparation method are the same as in Example 1.

[0069] Example 3

[0070] An organic solar cell and its preparation method are disclosed, which differ from Example 1 only in that the doping mass of ZnCF is 0.0005% (based on the mass sum of PM6 and N3 being 100%); the types of other materials, device structure and thickness, and preparation method are the same as in Example 1.

[0071] Comparative Example 1

[0072] An organic solar cell and its preparation method are disclosed. The only difference between this and Example 1 is that the photoactive layer is made of a combination of PM6 and N3 and does not contain ZnCF. The types of other materials, device structure and thickness, and preparation method are the same as in Example 1.

[0073] The performance of the organic solar cells provided in Examples 1-3 and Comparative Example 1 was tested using the following methods:

[0074] An IV meter was used under standard testing conditions (AM 1.5, light intensity 100mW / cm²). 2 The open-circuit voltage (Voc), short-circuit current (Jsc), fill factor (FF), and photoelectric conversion efficiency (PCE) of the organic solar cell were measured. The resulting IV test curves are shown in the figure below. Figure 2 As shown in Table 1:

[0075] Table 1

[0076] Example 1 0.842 26.40 73.44 16.40 Example 2 0.845 27.21 73.49 16.97 Example 3 0.848 25.68 74.48 16.23 Comparative Example 1 0.845 25.53 74.62 16.18

[0077] Depend on Figure 2 As shown in Table 1, compared with traditional PM6:N3 organic solar cells, the organic solar cell provided by this invention, by incorporating a specific amount of Lewis acid small molecule material di(pentafluorophenyl)zinc (ZnCF) into the photoactive layer, can greatly improve the performance of the entire device. The short-circuit current under standard test conditions is 25.68-27.21 mA / cm². 2The PCE was 16.23-16.97%, with a ZnCF doping ratio of 0.001% (Example 2). This optimized the performance of the organic solar cell, significantly improving the short-circuit current and increasing the photoelectric conversion efficiency (PCE) by 5% compared to Comparative Example 1. Therefore, the use of di(pentafluorophenyl)zinc-doped organic solar cells in this invention provides important insights for the subsequent fabrication of high-performance organic photovoltaic devices.

[0078] The applicant declares that the organic solar cell of the present invention, its preparation method, and its application are illustrated through the above embodiments. However, the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An organic solar cell, characterized in that, The organic solar cell comprises a conductive substrate, a first buffer layer, a photoactive layer, a second buffer layer, and a metal electrode arranged sequentially. The photoactive layer is made of a combination of electron donor materials, electron acceptor materials, and bis(pentafluorophenyl)zinc. Based on the total mass of the electron donor material and electron acceptor material being 100%, the mass of the di(pentafluorophenyl)zinc is 0.0005-0.01%.

2. The organic solar cell according to claim 1, characterized in that, The electron donor material includes polymer-based electron donor materials.

3. The organic solar cell according to claim 2, characterized in that, The electron donor material comprises a polymer containing electron-withdrawing conjugated units and electron-donating conjugated units.

4. The organic solar cell according to claim 2, characterized in that, The electron donor material includes PM6.

5. The organic solar cell according to claim 1, characterized in that, The electron acceptor material includes small molecule electron acceptor materials.

6. The organic solar cell according to claim 5, characterized in that, The electron acceptor material includes N3.

7. The organic solar cell according to claim 1, characterized in that, The mass ratio of the electron donor material to the electron acceptor material is 1:(0.2-5).

8. The organic solar cell according to claim 7, characterized in that, The mass ratio of the electron donor material to the electron acceptor material is 1:(1-1.5).

9. The organic solar cell according to claim 1, characterized in that, The thickness of the photoactive layer is 50-250 nm.

10. The organic solar cell according to claim 1, characterized in that, The conductive substrate is an ITO conductive substrate.

11. The organic solar cell according to claim 1, characterized in that, The material of the first buffer layer is a hole transport material.

12. The organic solar cell according to claim 11, characterized in that, The material of the first buffer layer includes PEDOT:PSS.

13. The organic solar cell according to claim 1, characterized in that, The thickness of the first buffer layer is 20-40 nm.

14. The organic solar cell according to claim 1, characterized in that, The material of the second buffer layer is an electron transport material.

15. The organic solar cell according to claim 14, characterized in that, The material of the second buffer layer includes PFN-Br and / or PNDIT-F3N.

16. The organic solar cell according to claim 1, characterized in that, The thickness of the second buffer layer is 10-20 nm.

17. The organic solar cell according to claim 1, characterized in that, The material of the metal electrode includes any one or a combination of at least two of the following: calcium, magnesium, barium, aluminum, silver, gold, copper, nickel, zinc, titanium, manganese, iron, platinum, or molybdenum.

18. The organic solar cell according to claim 17, characterized in that, The material of the metal electrode includes any one or a combination of at least two of silver, gold, and copper.

19. The organic solar cell according to claim 1, characterized in that, The thickness of the metal electrode is 70-120 nm.

20. A method for preparing an organic solar cell according to any one of claims 1-19, characterized in that, The preparation method includes: sequentially coating a first buffer layer material on a conductive layer of a conductive substrate, performing a first annealing treatment, coating a photoactive layer material, performing a second annealing treatment, coating a second buffer layer material, and setting a metal electrode to obtain the organic solar cell.

21. The preparation method according to claim 20, characterized in that, The method for coating the first buffer layer material includes spin coating.

22. The preparation method according to claim 20, characterized in that, The temperature of the first annealing treatment is 150-180℃.

23. The preparation method according to claim 20, characterized in that, The first annealing process takes 5-30 minutes.

24. The preparation method according to claim 20, characterized in that, The method for coating the photoactive layer material includes: drop-coating or spin-coating a solution of the photoactive layer material.

25. The preparation method according to claim 24, characterized in that, The sum of the concentrations of the electron donor material and the electron acceptor material in the solution is 10-30 mg / mL.

26. The preparation method according to claim 24, characterized in that, The solvent of the solution includes any one or a combination of at least two of chloroform, chlorobenzene, o-dichlorobenzene or o-xylene.

27. The preparation method according to claim 24, characterized in that, The solution also includes additives, which include any one or a combination of at least two of chloronaphthalene, diiodooctane, or diphenyl ether.

28. The preparation method according to claim 27, characterized in that, The volume percentage of the additive in the solution is 0.1-1%.

29. The preparation method according to claim 20, characterized in that, The temperature for the second annealing treatment is 80-100℃.

30. The preparation method according to claim 20, characterized in that, The second annealing process takes 5-20 minutes.

31. The preparation method according to claim 20, characterized in that, The method for coating the second buffer layer material includes spin coating.

32. The preparation method according to claim 20, characterized in that, The method for setting the metal electrode includes vapor deposition.

33. The preparation method according to claim 20, characterized in that, The preparation method specifically includes the following steps: (1) Spin-coat the first buffer layer material onto the conductive layer of the conductive substrate, and anneal at 150-180℃ for 5-30 min to obtain the first buffer layer; (2) A solution of photoactive layer material is drop-coated or spin-coated onto the first buffer layer obtained in step (1), and annealed at 80-100℃ for 5-20 min to obtain a photoactive layer; the sum of the concentrations of electron donor material and electron acceptor material in the solution is 10-30 mg / mL; (3) Spin-coat the second buffer layer material onto the photoactive layer obtained in step (2), and dry it to obtain the second buffer layer; (4) Deposit metal onto the second buffer layer obtained in step (3) to obtain a metal electrode and obtain the organic solar cell.

34. A photovoltaic module, characterized in that, The photovoltaic module includes an organic solar cell as described in any one of claims 1-19.

Citation Information

Patent Citations

  • Organic solar cell structure based on polypropylene as third element and manufacture method thereof

    CN109449297A

  • Ternary fullerene organic solar cell

    CN112259687A

  • Flexible organic solar cell and preparation method thereof

    CN114256421A

  • Organic solar cell based on small organic molecule additive and preparation method thereof

    CN106025079A

  • Up-conversion device based on alternating-current driving planar display unit

    CN111063680A